2009
DOI: 10.1080/01676830802421132
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid Contracture may Indicate Recurrent Basal Cell Carcinoma, even after Mohs’ Micrographic Surgery

Abstract: Mohs' micrographic surgery (MMS) is an effective means of margin control in the management of periocular basal cell carcinomas (BCC). We describe three cases of recurrent BCC that presented with progressive eyelid contracture after MMS. They illustrate high-risk factors for recurrence, namely large tumor size, medial canthal location, previous treatment, and aggressive histological features. Careful long-term surveillance with serial photography may identify early eyelid contracture and thus assist in the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Ong et al reported progressive eyelid contracture as an early sign of tumor recurrence but emphasized the difficulty in distinguishing it from scar tissue. 17 In our series, clinical examination findings were often nonspecific. Presenting signs of recurrence included contracture, ptosis, and medial canthus erythema.…”
Section: Discussionmentioning
confidence: 61%
“…Ong et al reported progressive eyelid contracture as an early sign of tumor recurrence but emphasized the difficulty in distinguishing it from scar tissue. 17 In our series, clinical examination findings were often nonspecific. Presenting signs of recurrence included contracture, ptosis, and medial canthus erythema.…”
Section: Discussionmentioning
confidence: 61%
“…12,16,17 This may be because of the close proximity of these sites to bone and cartilage or incomplete primary treatment. 18 Other risk factors for aggressive BCC are large size, neglected and longstanding tumor, aggressive histologic subtype as discussed previously, and perineural or perivascular invasion. 9, 16 Eyelid contracture has been reported as a clinical indicator of recurrent periocular BCC, even after MMS.…”
Section: Basal Cell Carcinomamentioning
confidence: 91%
“…9,16 Eyelid contracture has been reported as a clinical indicator of recurrent periocular BCC, even after MMS. 18 Other risk factors for aggressive BCC are large size, neglected and longstanding tumor, aggressive histologic subtype as discussed previously, and perineural or perivascular invasion. 12 When evaluating aggressive, high-risk, and neglected BCC, one must also consider the rare possibility of metastasis to the lymph nodes, lungs, and bone (incidence 0.003-0.55%).…”
Section: Basal Cell Carcinomamentioning
confidence: 91%
“…This finding has been reported as a sign of recurrence but not necessarily correlated with orbital invasion. 3 It is a separate entity from postreconstruction contraction. Anecdotally, one of the senior authors (D.S.)…”
Section: To the Editormentioning
confidence: 99%